PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP NILAI PERUSAHAAN DI MEDIASI PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR KIMIA YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Frangky Yosua Sitorus (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
This study has a research objective, namely to find out the effect of cash turnover and accounts receivable turnover on firm value in mediating profitability. The approach in this study is to use a quantitative approach with a population of 13 companies listed in the Chemical Sub Sector on the Indonesia Stock Exchange (IDX) in the 2018-2022 period. Sample selection is used using purposive sampling method. So that the sample in this study amounted to 10 Chemical Sub Sector companies. This type of research data is secondary data. Data in the form of financial reports and company annual reports obtained from the Indonesia Stock Exchange website. The data collection technique in this study is documentation. The data analysis technique was carried out using the path analysis method. The findings of this study are that there is a significant effect of cash turnover on firm value, but it does not have a significant effect on profitability, as well as there is no significant effect of receivables turnover on company value or profitability. However, this study concludes that there is a significant effect of profitability on firm value.